Adhesive Property and Road Performance Evaluation of Asphalt Overlay Pavement with Geotextile Interlayer - Haiwei Zhang; Bowei Sun; Yongxiang Li; Yanli Li (Advances in Materials Science and Engineering)
Geosynthetic interlayer systems are effective techniques to control reflective cracking and have better waterproof performance in damaged asphalt pavements. The interlayer bonding performance is critical to its function. This research investigated the interfacial adhesive property and road performance of asphalt overlay with geotextile interlayer. First, shear damage energy characteristics of geotextile interlayer have been investigated by varying tack coat types (SBS-modified asphalt, virgin asphalt, and emulsified asphalt), application rates (0.3 kg/m2–1.2 kg/m2), spraying times (1–2), upper mixture paving temperature (140°C–180°C), service temperature (5°C–45°C), and soaking time (0 h–96 h). In addition, bending fatigue tests, rutting tests, and semicircular bending tests were carried out to evaluate the comprehensive road performance of the asphalt overlay. The results showed that the interface adhesive property of asphalt overlay with geotextile interlayer using SBS-modified asphalt is best when the application rate is 0.8 kg/m2. The higher paving temperature is beneficial for the geotextile interlayer adhesion performance when the SBS-modified asphalt is sprayed at one time, while the paving temperature has almost no effect when the SBS-modified asphalt is sprayed at two times. The geotextile interlayer adhesion performance is less affected by temperature and more affected by water immersion. Compared with the common asphalt overlay types, the asphalt overlay with geotextile interlayer using SBS-modified asphalt shows better overall performance.